Technology foresight for hydrogen society transition in Japan: Approach of GTAP-E-Power model - Michael C. Huang; Yoko Iwaki; Ming-Huan Liou (Asian Development Bank Institute (ADBI), 2023)
With its portable, storable, and zero-emission features, hydrogen energy is regarded as one of the most promising alternative energies for the next generation. Along with developing hydrogen technology applications, Japan's pilot experiments have demonstrated the feasibility of a hydrogen society. However, empirical studies are still scarce and limited to energy efficiency analysis or cost-benefit analysis, and lack inclusive discussion contributing to the evidence-based approach targeting policy implementation of the hydrogen roadmap. The research aims to provide a quantitative impact assessment of Japan's hydrogen society by applying the GTAP-E-Power model with the technology foresight parameters of 2025-2035 sourced from the SciREX Policy Intelligence Assistance System - Economic Simulator (SPIAS-e) to investigate the change in output, price, and defragmentation of supply chains of energy sectors, as well as the emission of carbon dioxide from domestic and foreign firms. In the scenario of transitioning the existing fossil power of coal, natural gas, crude oil, and other renewable energies including solar and wind power, the simulation results demonstrated that the CO2 emission by domestic firms in the transportation and service sectors could be reduced by 3.3% and 2.3%, respectively, for power generation sectors, a total equivalent to 26.6 million tons thanks to the improvement in energy efficiency. In comparison, the export of transport equipment and energy-intensive sectors increased by 6.5% and 5.6%, respectively. Moreover, the welfare analysis of equivalent variations of Japan's hydrogen society showed an increase of 75,696 million and a 1.3% growth in GDP.
Keywords: C68; R11; O13; O14; Q47; 330; hydrogen society; CO2 emission; SPIAS-e; net-zero society; GTAP-E-Power